Implementation of a remote control application for elderly people in Brazil: Analysis of the factors involved in the use of a technological innovation related to telecare - Delgado, Cristina Nieves Perdomo [UNESP]; Paschoarelli, Luis Carlos [UNESP] (Stichting Liliane Fonds, 2020)
Purpose: The rapid ageing of the Brazilian population highlights the importance of new assistive technologies. The objective of this study was to analyse the positive and negative factors involved in the implementation of a Remote Care App for the elderly in Brazil. Method: A qualitative method as been used, based on discussion groups involving 30 older Brazilian people who participated via a Telecare App. Results: The results obtained highlight positive factors such as security, independence and personal tranquillity, and negative factors such as the privacy of the elderly, the social differences of Brazil, and the design and utility of the App. Conclusion: Discourses on ageing at home using assistive technologies are cultural resources from which older people can make sense of their experience as users of Remote Care. It is also relevant information for the improvement of public policies aimed at caring for the elderly, by considering assistive technologies as factors for independent ageing.
Keywords: Assistive technology; Elderly people; Independence; Telecare